Effects of the voltage unbalance on power factors considering the fairness perspective for billing purposes - Brasil, Victor do Prado (2023)
Tese (doutorado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2023.